Surgical management of hidradenitis suppurativa - Gierek, Marcin; Ochała-Gierek, Gabriela; Kitala, Diana; Łabuś, Wojciech; Bergler-Czop, Beata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Hidradenitis suppurativa (HS) is a chronic disease, which causes painful discomfort. The main regions involved in this disease are axillary, inguinal and perianal. The etiology is unknown at present. It is suggested that genetics, smoking and diabetes are involved in HS. General treatment consists of antibiotics and anti-inflammatory biological drugs. HS is a multidisciplinary disease, which involves surgical treatment as well. We would like to present surgical treatment in HS. Deroofing and drainage/incisions are the most frequent techniques in general surgery departments. The article describes additional techniques such as skin grafts and flaps. We conclude that local flaps are the best choice in surgical treatment.